Intraperitoneal Therapy for Ovarian Cancer - Alberts, David; Clouser, Mary C.; Hess, Lisa M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Intraperitoneal chemotherapy is increasingly being used as first-line treatment for ovarian cancer. Nevertheless, it is difficult for the oncologist to find a definitive text that documents both the fundamental methods required to optimize therapy and the up-to-date results of phase I, II, and III clinical trials. With this in mind, the editors of Intraperitoneal Therapy for Ovarian Cancer have assembled a team of highly experienced clinicians and researchers to cover every aspect of the subject. The topics addressed include treatment principles, patient, drug, and catheter selection, administration guidelines, the role of hyperthermia, supportive care requirements, novel drugs, and the most recent results of clinical trials. This book will be an invaluable source of information for both practicing clinical oncologists and oncologists in training, oncologists and basic and translational scientists in training.
Current Chemotherapy of Ovarian Cancer -- Principles of Intraperitoneal Chemotherapy -- Intraperitoneal Chemotherapy: Phase III Trials -- Criteria for Using Intraperitoneal (IP) Chemotherapy for Advanced Ovarian Cancer -- Selection and Placement of Intraperitoneal Catheters for IP Chemotherapy for Ovarian Cancer -- Selection of Drugs for Intraperitoneal Chemotherapy for Ovarian Cancer -- Administration Guidelines for Intraperitoneal Chemotherapy for Ovarian Cancer -- Novel Drugs for Intraperitoneal Therapy for Ovarian Cancer -- Cytoreductive Surgery and Perioperative Intraperitoneal Chemotherapy: An Ongoing Research Effort -- Health-Related Quality of Life and Patient-Reported Outcomes.
Keywords: Oncology .; Oncology